THE LEVEL OF PREPAREDNESS OF THE SANGAJI VILLAGE COMMUNITY TO OVERCOME THE THREAT OF ROB - Salam, Ramdani; Safitri, Yuni Andriyani (Geographica: Science and Education Journal, 2024)
Community preparedness in facing flood disasters is a multifaceted issue that involves understanding resilience, increasing knowledge, and implementing effective interventions. Various studies have highlighted the importance of systematic assessment and community involvement to improve the level of preparedness, including this study. This study was conducted with the aim of determining the level of preparedness of the coastal community of Sangaji Village in facing the threat of tidal flooding due to tidal waves. This study uses a quantitative descriptive approach or method. To limit the research area, only communities living in the coastal border area within a radius of 200 meters were used as samples in this study with a quota of 10% of the total number of families so that 40 families were obtained as respondents. Based on data analysis, it was found that the level of community preparedness at the research location was included in the very good category (82.02%). The preparedness parameters assessed if described from the largest to the smallest level are the early warning system (96%), Emergency Response Plan (80.5%), Knowledge (80.25%), Resource mobilization (78.25%) Attitude (72.5%). Using loudspeakers from prayer rooms and mosques or ringing electric poles with objects so that they produce sound as methods used in the early warning system which are considered effective. However, the community's attitude is sometimes indifferent in facing preparation, in the form of simulations, socialization related to disasters in general.